Synthesis of 8-Methoxyquinoline-5-Amino Acetic Acid and its Herbicidal Potential - E., Adewole; O.T., Oke; A., Ojo (Journal of Advance Research in Applied Science (ISSN 2208-2352), 2015)
The quinoline skeleton is often used for the design of many synthetic compounds with diverse pharmacological properties. 8-Methoxyquinoline 5-amino acetic acid was synthesized from coupling of monochloroacetic acid with 5-amino-8-methoxyquinoline. The IR showed – OH stretch absorption and amino group (-NH) which is not too prominent at 3450cm-1 and 3300cm-1, carbonyl (C=O) absorption depicts at 1614cm-1. The herbicidal activity of the synthesized compound was tested on the weeds and after 11 days of application, the weeds have dried completely indicating the efficacy of the compound.